Predictability of keeping quality of strawberry batches - Schouten, Rob E.; Kessler, Daniela; Orcaray, Luis; van Kooten, Olaf (Postharvest biology and technology, 2002)
Postharvest life of strawberries is largely limited by Botrytis cinerea infection. It is assumed that there are two factors influencing the batch keeping quality: the Botrytis pressure and the resistance of the strawberry to infection. The latter factor will be discussed in this article. A colour model is presented that describes the development of red colour and anti-fungal function of individual strawberries over time. The model was fitted to colour data from strawberries grown at two different nutrient densities (EC) and stored per batch at 5, 10 or 16 °C and constant vapour pressure deficit after harvest. A batch was defined as all strawberries from one EC and one harvest. Spoilage per batch was recorded daily during storage. The fitted initial spoilage per batch was found to relate to the fitted average amount of precursor of both the colour and the anti-fungal compounds. Batch keeping quality could be derived from the initial batch colour distributions for the low nutrient batches. Also, batch keeping quality correlated highly with the time between harvest dates for the low EC batches. An explanation for the ability to link colour distributions to keeping quality without having to use a term describing the pH is presented from pigment HPLC measurements of sub-batches. Indications that the colour distributions of high EC batches may be subject to substantial co-pigmentation are presented. For a practical implementation of predicting keeping quality of batches additional research is needed, especially regarding different Botrytis pressures between greenhouses.